Single‐cell RNA sequencing reveals the epithelial cell heterogeneity and invasive subpopulation in human bladder cancer - Lai, Huadong; Cheng, Xiaomu; Liu, Qiang; Luo, Wenqin; Liu, Mengyao; Zhang, Man; Miao, Juju; Ji, Zhongzhong; Lin, Guan Ning; Song, Weichen; Zhang, Lianhua; Bo, Juanjie; et al. (International journal of cancer, 2021)
Bladder cancer represents a highly heterogeneous disease characterized by distinct histological, molecular and clinical phenotypes, and a detailed analysis of tumor cell invasion and crosstalks within bladder tumor cells has not been determined. Here, we applied droplet‐based single‐cell RNA sequencing (scRNA‐seq) to acquire transcriptional profiles of 36 619 single cells isolated from seven patients. Single cell transcriptional profiles matched well with the pathological basal/luminal subtypes. Notably, in T1 tumors diagnosed as luminal subtype, basal cells displayed characteristics of epithelial‐mesenchymal transition (EMT) and mainly located at the tumor‐stromal interface as well as micrometastases in the lamina propria. In one T3 tumor, muscle‐invasive tumor showed significantly higher expression of cancer stem cell markers SOX9 and SOX2 than the primary tumor. We additionally analyzed communications between tumor cells and demonstrated its relevance to basal/luminal phenotypes. Overall, our single‐cell study provides a deeper insight into the tumor cell heterogeneity associated with bladder cancer progression. What's new? Extensive heterogeneity in bladder cancer has inspired novel approaches to the investigation of underlying mechanisms, including genomic and phenotypic single‐cell analyses. In this single‐cell characterization of tumor cell heterogeneity in bladder cancer, basal‐like tumor cells were found to possess epithelial‐to‐mesenchymal transition (EMT) features, including enrichment of EMT‐associated genes. Basal‐like cells further exhibited a potential to generate luminal daughter cells, making them possible precursors for local invasion. In addition, aggressive cells with upregulation of stemness‐related genes were observed in a muscle‐invasive T3‐stage tumor. The findings suggest that invasive cell subsets within bladder cancers may serve a significant role in disease progression.